Concise Review: Are Stimulated Somatic Cells Truly Reprogrammed into an ES/iPS-Like Pluripotent State? Better Understanding by Ischemia-Induced Multipotent Stem Cells in a Mouse Model of Cerebral Infarction - Takayuki Nakagomi; Akiko Nakano-Doi; Aya Narita; Tomohiro Matsuyama (Stem Cells International)
Following the discovery of pluripotent stem (PS) cells such as embryonic stem (ES) and induced pluripotent stem (iPS) cells, there has been a great hope that injured tissues can be repaired by transplantation of ES/iPS-derived various specific types of cells such as neural stem cells (NSCs). Although PS cells can be induced by ectopic expression of Yamanaka’s factors, it is known that several stimuli such as ischemia/hypoxia can increase the stemness of somatic cells via reprogramming. This suggests that endogenous somatic cells acquire stemness during natural regenerative processes following injury. In this study, we describe whether somatic cells are converted into pluripotent stem cells by pathological stimuli without ectopic expression of reprogramming factors based on the findings of ischemia-induced multipotent stem cells in a mouse model of cerebral infarction.